2014
DOI: 10.1371/journal.pone.0091551
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Abundance of Tumor-Infiltrating Regulatory T Cells Is Correlated with the Progression and Prognosis of Pancreatic Ductal Adenocarcinoma

Abstract: CD4+CD25+Foxp3+ regulatory T cells (Tregs) can inhibit cytotoxic responses. Though several studies have analyzed Treg frequency in the peripheral blood mononuclear cells (PBMCs) of pancreatic ductal adenocarcinoma (PDA) patients using flow cytometry (FCM), few studies have examined how intratumoral Tregs might contribute to immunosuppression in the tumor microenvironment. Thus, the potential role of intratumoral Tregs in PDA patients remains to be elucidated. In this study, we found that the percentages of Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
154
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(164 citation statements)
references
References 45 publications
8
154
1
1
Order By: Relevance
“…Immunohistochemistry was performed as previously described [34]. SPHK1 antibody (1:100 dilution, Abcam) was used as the primary antibody.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described [34]. SPHK1 antibody (1:100 dilution, Abcam) was used as the primary antibody.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…In hepatocellular carcinoma (HCC) and pancreatic cancer, accumulation of Treg has been directly associated with poor prognosis. 22,[26][27][28] Little is known so far about the mechanisms leading to CCL22 expression in the cancer tissue. In our study, we show that tumor cell-derived IL-1a specifically induces CCL22 expression in tumor-infiltrating dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that decreased numbers of those cells is associated with impairment of immunity against tumors, which results in tumor progression. In fact, several studies have demonstrated that the numbers of tumor infiltrating lymphocytes, such as CD4 + and CD8 + T cells, were associated with prognosis in some cancers [16-18]. Furthermore, a close correlation between decreased numbers of immune cells, such as NK cells, B cells, and gamma-delta T cell, and poor prognosis has also been demonstrated in both peripheral blood and cancer tissue for some cancer types [19-21].…”
Section: Discussionmentioning
confidence: 99%